2020
DOI: 10.1177/0004563220972539
|View full text |Cite|
|
Sign up to set email alerts
|

Correlating arterial blood gas, acid–base and blood pressure abnormalities with outcomes in COVID-19 intensive care patients

Abstract: Background: During the outbreak of coronavirus disease 2019 (COVID-19) many studies have investigated laboratory biomarkers in management and prognostication of COVID-19 patients, however to date, few have investigated arterial blood gas (ABG), acid-base and blood pressure (BP) patterns. The aim of the study is to assess the ABG and acid-base patterns, BP findings and their association with the outcomes of COVID-19 patients admitted to an intensive care unit (ICU). Methods: A single-centre retrospective, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
1
10

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 31 publications
0
47
1
10
Order By: Relevance
“…Chloride homeostasis has been briefly discussed in previous studies without finding any prognostic value of the level during admission ( 26 ). In patients admitted to the ICU, alkalosis has been seen in arterial blood ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chloride homeostasis has been briefly discussed in previous studies without finding any prognostic value of the level during admission ( 26 ). In patients admitted to the ICU, alkalosis has been seen in arterial blood ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previos studies with COVID-19 patients have also reported low pH levels in arterial blood gaz analyses and related this situation to respiratory acidosis caused by lung damage [29,30,31]. Another study in COVID-19 patients in the ICU have shwon that relatively higher arterial blood pH is strongly correlated with survival [32].…”
Section: Discussionmentioning
confidence: 99%
“…Наличие выраженного алкалоза при поступлении, с низкими цифрами растворенного кислорода, высокой углекислоты лактата у пациентов с новой коронавирусной инфекцией фиксировалось также и в других исследованиях. При этом выраженность исходного алкалоза коррелировала с летальностью [6].…”
Section: обмен клиническим опытомunclassified
“…Исследователями определён предиктор выживаемости -повышенный уровень pH. Средние уровни калия, натрия, лактата, креатинина и мочевины в группах выживших и умерших пациентов не имели статистических различий [6].…”
Section: обмен клиническим опытом оригинальное исследование / Original Researchunclassified
See 1 more Smart Citation